Adoption of Building Information Modelling in Malaysia Road Construction. Issue 1 (October 2020) - Yung, A T B; Aminudin, E; Liat, C N S; Neardey, M; Zakaria, R; Hamid, A R A; Ahmad, F; Yong, L Y
Abstract: Building Information Modeling (BIM) has changed the road development industry in the most recent decades. In spite of the fact that there are activities by administration of Malaysia to improve the selection of BIM in road development, yet the usage of BIM is still not true to form because of misty guide of BIM reception plan in Malaysia. Along these lines, it is essential to recognize the issues and difficulties in usage of BIM so as to improve the selection of BIM in this industry. This paper plans to analyze the street development industry in Malaysia to build up an unmistakable comprehension about BIM execution and to give the key arrangements and system for street development industry to expand the reception of BIM in Malaysia. This paper has built up broad BIM understanding which makes ready for the investigation by means of subjective and quantitative technique where the information is gathered through study poll among the street development partners in Malaysia and the gathered information is dissected with Average Index utilizing SPSS Software. The outcomes indicated the degree of current BIM usage in Malaysia street development industry is still extremely low and the issues and difficulties of BIM are distinguished in six zones incorporate specialized, process, legitimate, return of venture, government and individuals. Government has been recognized to assume a significant job in offering help to improve appropriation of BIM in Malaysia. The result of this investigation is communicated as a system for the usage of BIM in Malaysia involving issues that require thought for association to advance on BIM development stepping stool. This investigation clears a firm establishment for association to settle on choice in the appropriation of BIM in street development inside the general association structure.